Preterm newborns at Kangaroo Mother Care: a cohort follow-up from birth to six months - Menezes,Maria Alexsandra da S. (2014)
OBJECTIVE:To evaluate clinical outcomes, growth and exclusive breastfeeding rates in premature infants assisted by Kangaroo Mother Care at birth, at discharge and at six months of life.METHODS: Prospective study of a premature infants cohort assisted by Kangaroo Mother Care in a tertiary public maternity in Northeast Brazil with birth weight ≤1750g and with clinical conditions for Kangaroo care.RESULTS: The sample was composed by 137 premature infants, being 62.8% female, with average birth weight of 1365±283g, average gestational age of 32±3 weeks and 26.2% were adequate for gestational age. They have been admitted in the Kangaroo Ward with a median of 13 days of life, weighing 1430±167g and, at this time, 57.7% were classified as small for corrected gestational age. They were discharged with 36.8±21.8 days of chronological age, weighing 1780±165g and 67.9% were small for corrected gestational age. At six months of life (n=76), they had an average weight of 5954±971g, and 68.4% presented corrected weight for gestational age between percentiles 15 and 85 of the World Health Organization (WHO) weight curve. Exclusive breastfeeding rate at discharge was 56.2% and, at six months of life, 14.4%.CONCLUSIONS: In the studied sample, almost two thirds of the children assisted by Kangaroo Mother Care were, at six months of life, between percentiles 15 and 85 of the WHO weight curves. The frequency of exclusive breastfeeding at six months was low.